The omission of intentional primary site radiation following transoral robotic surgery in 59 patients: No local‐regional failures. Issue 2 (1st December 2021) - Dhere, Vishal R.; Escott, Chase E.; Tian, Sibo; Switchenko, Jeffrey M.; Bell, James P.; Stokes, William A.; McDonald, Mark W.; Magliocca, Kelly R.; Boyce, Brian J.; Kaka, Azeem S.; Steuer, Conor E.; Saba, Nabil F.; et al.
Abstract: Background: We assessed locoregional control with omission of intentional primary site radiation after transoral robotic surgery (TORS) and quantified nontargeted primary site dose. Methods: Following Institutional Review Board (IRB) approval, patients treated with primary TORS resection for squamous cell carcinomas of the oropharynx were reviewed. Patients with cT1‐2 tumors, >2 mm margins, in whom the surgeon resected the primary without revising specimen‐driven margins, qualified for omission of primary site radiation. Results: From 2014 to 2019, 112 patients met criteria. Fifty‐nine (52%) patients did not receive radiation targeting the primary site; of whom, 22 received no radiation. In this group, there were no local failures; mean age was 58 years and median follow‐up was 25 months. Thirty‐seven patients received adjuvant radiation targeting the neck, mean bystander dose to the primary site was 28.8 Gy (range, 13.3–50.6 Gy). Conclusion: In a 59 patient population, omission of radiation to the primary site after TORS resulted in no locoregional failures.